The Moderating Role of Willpower as a Personality Trait in the Relationship Between Social Influence and Moral Disengagement Contradiction - Okan, Nesrullah (Wiley, 2025)
Objective:The objective of this study is to examine the moderating role of willpower, conceptualized as a personality trait, in the relationship between social influence and moral disengagement towards migrants. The mediating role of spiritual contradiction is also investigated to understand the interplay between individual traits, moral contradictions, and external social pressures.Method:Data were collected from 720 participants using validated self-report measures. Structural equation modeling (SEM) was employed to test the proposed relationships among social influence, moral disengagement, spiritual contradiction, and willpower. Moderation and mediation analyses were conducted to evaluate the hypothesized model.Results:The findings reveal that social influence significantly predicts moral disengagement. This relationship is partially mediated by spiritual contradiction, which amplifies disengagement by reflecting tensions between internal moral values and external norms. In addition, the study found that willpower moderates this relationship by reducing the negative impact of social influence on moral disengagement. Individuals with higher levels of willpower demonstrate greater resistance to moral disengagement and maintain moral consistency despite external pressures and moral contradictions.Conclusions:This study underlines the pivotal function of personality traits and spiritual dimensions in shaping moral processes. The findings have practical applications for ethical education and interventions designed to enhance moral resilience in varied social contexts.
Keywords: attitudes towards immigrants; moral contradiction; moral disengagement; personality; social influence; willpower